Georges Perec’s Novel “W, Ou Le Souvenir D’enfance” as Autofiction (Proceedings of Southern Federal University. Philology, 2020)
This article attempts to define the complex relationship of truth and fiction in the autobiographical context of Georges Perec’s novel W, or the Memory of Childhood (1975). Georges Perec is a classic of French literature who immigrated as a Polish Jew, whose family suffered the horrors of the Second World War. In France, his literary heritage remains relevant to scholars, although many works are already devoted to him, but in Russia he is still little known and poorly understood. Within his most famous novel W, or the Memory of Childhood Perec presents two stories that are intertwined in a special way: autobiographical and fictional. The purpose of this article is to establish not just textual differences between two stories that have deceptive paratextual boundaries, but to establish how the factual and fictional mutation occurs in Perec’s autobiographical text, often referred to by researchers as autofiction. Autofiction is applied to almost all French literature of 60-70s as a certain literary tendency of comprehending and aesthetization of infraordinary life. Thus, the study of autofiction in Perec’s works allows us to better understand not only his poetics, but also the typical features of the literature of that time period. The author of the article considers the genre features of the work, its structure, the essence of various narrators. The article concludes that the writer has a complex perception of the relationship between truth or fact and fiction, expressed in the form of autofiction, not because of the desire to play with the reader, but because of the game with its own memory, which reveals the real indistinguishability of some memories as false or true.Key words: Georges Perec, autofiction, genre, autobiography, fiction.DOI 10.18522/1995-0640-2020-2-171-179